1998
DOI: 10.1038/sj.bjp.0701646
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the development of morphine tolerance by U‐50,488, an AVP antagonist or MK‐801 in the rat hippocampal slice

Abstract: 1 In this study, we investigated the eects of dierent drugs (a k-opioid receptor agonist U-50,488, a vasopressin receptor antagonist dPTyr(Me)AVP or an N-methyl-D-aspartate (NMDA) receptor antagonist MK-801) on the development of morphine tolerance in rat hippocampal slices. 2 Hippocampal slices (450 mm) of Sprague-Dawley rats (250 ± 300 g) were used. Slices were continuously superfused with arti®cial CSF or drugs at 1 ml min 71 . Nichrome wire electrodes were placed in the Schaer-collateral pathway and used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…MK-801 inhibited the development of tolerance, as reflected in analgesia, and prevented the increase in protein kinase C, demonstrating a nice correlation between changes in behavior and neurochemistry. Additional studies have explored cellular changes in the spinal cord (Wong et al 1996;Le Guen et al 1999), which may have relevance to tolerance to the analgesic effect of opiates, as well as specific brain regions (Trujillo et al 1991;Garcia and Harlan 1993;Makimura et al 1996Makimura et al , 1997Su et al 1998), which may have relevance to other aspects of opiate tolerance, sensitization or physical dependence (Table 4). Together, these studies demonstrate 1) that the development of opiate tolerance, sensitization and physical dependence are accompanied by cellular changes in the brain and spinal cord that may reflect the neural plasticity underlying the behavioral changes, and 2) that these cellular changes can be inhibited by NMDA receptor antagonists in a manner that parallels the behavioral changes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MK-801 inhibited the development of tolerance, as reflected in analgesia, and prevented the increase in protein kinase C, demonstrating a nice correlation between changes in behavior and neurochemistry. Additional studies have explored cellular changes in the spinal cord (Wong et al 1996;Le Guen et al 1999), which may have relevance to tolerance to the analgesic effect of opiates, as well as specific brain regions (Trujillo et al 1991;Garcia and Harlan 1993;Makimura et al 1996Makimura et al , 1997Su et al 1998), which may have relevance to other aspects of opiate tolerance, sensitization or physical dependence (Table 4). Together, these studies demonstrate 1) that the development of opiate tolerance, sensitization and physical dependence are accompanied by cellular changes in the brain and spinal cord that may reflect the neural plasticity underlying the behavioral changes, and 2) that these cellular changes can be inhibited by NMDA receptor antagonists in a manner that parallels the behavioral changes.…”
Section: Discussionmentioning
confidence: 98%
“…Comp and protein kinase C in pons/medulla (tolerance); Withdrawal-induced increase in norepinephrine release in hippocampus (dependence) Su et al (1998) MK-801 Non-comp Rat Morphine-induced increase in population spike amplitude hippocampal in hippocampus (tolerance) slice Le Guen et al (1999) MK-801 Non-comp Rat Morphine suppression of carageenin-induced c-Fos LY 235959 Comp expression in spinal cord (tolerance) phine-induced effects. A second study of note is that of Bilsky and coworkers (1996).…”
Section: Discussionmentioning
confidence: 99%
“…In response to analgesic tolerance caused by repeated administration of morphine, KOR agonists such as U-50488H (Tao et al 2000;Tokuyama et al 2007) and dynorphin (Brugos et al 2004) inhibit the development of tolerance at a dose at which no analgesic effect is observed. Moreover, this inhibitory effect was antagonized by nor-binaltorphimine (nor-BNI), a KOR antagonist, suggesting that KOR plays an important role in the mechanism of inhibition of morphine tolerance (Su et al 1998). Our previous data have also shown that inhibition of morphine tolerance under chronic pain conditions is blocked by antisense oligodeoxynucleotide directed against KOR (Tokuyama et al 2007).…”
mentioning
confidence: 95%
“…Nalbuphine was purchased from Mallinckrodt Inc. (St Louis, Missouri, U.S.A.). U‐50,488H was a gift from Dr Chen‐Yu Cheng, who prepared it as described in our previous paper (Su et al ., 1998). All other chemicals were supplied by Sigma (St Louis, MO, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%